The Role of Hexagonal Boron Nitride (h‐BN) in Enhancing Electrolytes for Safer and Efficient Lithium‐Based Batteries - Gulsah Yaman Uzunoglu; Sahin Coskun; Recep Yuksel (ChemElectroChem)
Hexagonal boron nitride (h‐BN), with its unique structural and thermal properties, has emerged as a versatile material capable of addressing challenges such as thermal instability, dendrite formation, and limited ionic conductivity across liquid, gel polymer, and solid‐state electrolytes (SSEs) for high‐performing lithium ion and lithium metal batteries (LMBs). In liquid electrolytes, h‐BN improves ionic mobility and suppresses side reactions, while in gel polymer electrolytes (GPEs), it enhances mechanical flexibility and thermal stability. SSEs benefit from h‐BN's ability to suppress dendrites, reinforce mechanical strength, and optimize interfacial compatibility, making it a key enabler for next‐generation battery technologies. Despite its promise, challenges such as dispersion uniformity, cost, and interfacial complexity must be addressed. Future directions, including the development of multifunctional architectures, dynamic electrolytes, and sustainable synthesis methods, are discussed to guide the integration of h‐BN in emerging energy storage systems. This perspective article explores the multifunctional roles of h‐BN, highlighting its contributions to enhancing ionic transport, thermal management, and interfacial stability. By presenting a comprehensive overview of h‐BN's role in electrolytes, this work aims to inspire further research into its potential to revolutionize energy storage technologies.